Metal delivering into plasma of cathode flare at forced explosion of point emitters; Proceedings of the Vth International Symposia on Discharge and Electrical Insulation in Vacuum, Poznan, august-september 1972 - Mesyats G. A. Gennady Andreyevich; Bazhenov G. P.; Litvinov E. A.; Proskourovsky D. I.; Yankelevitch E. B. (1972, 1972)
В фонде НТБ ТПУ отсутствует